2018
DOI: 10.3390/molecules23030518
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin and Cancer Hallmarks

Abstract: Melatonin is a natural indoleamine produced by the pineal gland that has many functions, including regulation of the circadian rhythm. Many studies have reported the anticancer effect of melatonin against a myriad of cancer types. Cancer hallmarks include sustained proliferation, evading growth suppressors, metastasis, replicative immortality, angiogenesis, resisting cell death, altered cellular energetics, and immune evasion. Melatonin anticancer activity is mediated by interfering with various cancer hallmar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
148
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 176 publications
(149 citation statements)
references
References 150 publications
0
148
0
1
Order By: Relevance
“…In our patients who self‐donate stem cells, even sleep prior to bone marrow harvest may be important for the recovery of blood counts post‐HDCT/aSCR. In addition, melatonin, a hormone of the pineal gland that helps regulate sleep–wake cycles, is a powerful free radical scavenger with oncostatic activity . In preclinical and clinical studies, melatonin supplementation was shown to improve stem cell survival in recipients, and to ameliorate damage to multiple organs from radiation and HDCT .…”
Section: Discussionmentioning
confidence: 99%
“…In our patients who self‐donate stem cells, even sleep prior to bone marrow harvest may be important for the recovery of blood counts post‐HDCT/aSCR. In addition, melatonin, a hormone of the pineal gland that helps regulate sleep–wake cycles, is a powerful free radical scavenger with oncostatic activity . In preclinical and clinical studies, melatonin supplementation was shown to improve stem cell survival in recipients, and to ameliorate damage to multiple organs from radiation and HDCT .…”
Section: Discussionmentioning
confidence: 99%
“…In an in vitro study, melatonin suppressed the growth of human cancer cell lines by inhibition of specific phases of cell cycles. Also, melatonin decreases metastasis and invasion by changing the expression of adhesion molecules and intracellular communication . Other oncostatin actions of melatonin in various cancers include the modulation of transactivation and expression of estrogen receptor (ERa), calcium/calmadulin and protein kinase C activity, cytoskletal structure, redox status of cells, the activity of aromatase and telomerase, and fatty acid transportation and metabolism …”
Section: Anticancer Features Of Melatoninmentioning
confidence: 99%
“…Melatonin has been demonstrated to relieve many cancer complications such as angiogenesis, tumor proliferation, and metastasis. 67,68 Melatonin exhibits anticancer features through many functions including inhibition of fatty acids and growth factor uptake by tumor cells, suppression of the activity of telomerase (via decreasing the length of telomere), induction of apoptosis, inhibition of endothelin-1 synthesis (which is an angiogenic factor), increased growth of blood vessels, and regulation of some tumor suppressors' expression, such as TP53. 69,70 A large number of in vitro and in vivo studies have confirmed the antitumor properties of melatonin.…”
Section: Anticancer Features Of Melatoninmentioning
confidence: 99%
See 1 more Smart Citation
“…Melatonin possesses multiple pathophysiological properties, including circadian rhythm regulation, antioxidant activity, immune defense, and inflammation and cancer prevention [7,8]. Accumulating evidence has suggested that melatonin's antioxidant activity might be useful in treating diabetes and attenuating diabetic nephropathy [9,10].…”
Section: Introductionmentioning
confidence: 99%